Synthesis and characterization of uniform fine particles of pure and chromium-substituted manganese ferrite with low dielectric losses. Issue 16 (December 2016) - Akhtar, Khalida; Gul, Muhammad; Haq, Ikram Ul; Khan, Rafaqat Ali; Khan, Zia Ullah; Hussain, Abid
Abstract: Pure and chromium doped manganese ferrite ( Mn Cr x Fe 2 − x O 4 with x=0.0, 0.2, 0.6, 1.0) uniform particles were synthesized by chemical precipitation in surfactant-free aqueous medium and characterized by various physical techniques such as SEM, XRD, EDX, TG/DTA, FTIR and LCR meter. Our results showed that calcination up to 1100 °C could not initiate a single phase formation and particle morphology was distracted in case of undoped sample. However, replacement of some of Fe 3+ ions with Cr 3+ ions resulted single spinel phase with controlled morphology and lowered ferritization temperature. This effect was attributed to the increased ion mobility, which led to the enhanced solid-solid interactions between the metal oxides in the solid matrix. The crystallite size of the calcinated products was found to increase linearly with increase in calcination temperature and Cr 3+ content in the solid sample. Various crystallographic properties were calculated for the selected solids, which are discussed on the basis of difference in the ionic radii of the replacing ions. Dielectric parameters showed relaxation behavior with frequency beyond 2 GHz. AC conductivity study showed involvement of small polarons in conduction mechanism. The significantly lowered dielectric losses and high quality factor enable the synthesized material to be used in hi-tech applications.